Drug Resistance Tuberculosis Epidemic in India: A Review - Pranay Deotale; Nitish Mondal (Online Journal of Health & Allied Sciences, 2023)
Background: The emergence of drug-resistant tuberculosis (DR-TB), a challenging health condition to treat, poses serious problems for public health in India. Unfavorable socioeconomic conditions, limited access to healthcare and insufficient diagnostic tools all increase vulnerability. Comorbidities also make it more difficult to treat TB and promote the development of DR-TB. Objectives: The primary goal of this review study was to focus particularly on the DR-TB epidemic in India. Our understanding of DR-TB will be expanded as a result of this study, which will also make it easier to develop focused interventions and public health regulations to deal with this problem. Methods: A meticulous systematic literature review was carried out using a wide range of electronic databases from around the world, including reputable sources. Results: The prevalence of DR-TB is rising over time. The main factors contributing to the disease's rising prevalence are genetic changes in Mycobacterium tuberculosis, and the appearance of comorbidities in TB patients. In contrast, these elements impair immunity, increase the likelihood of side effects from treatment, and promote the spread of DR-TB. Conclusion: To address the problems brought on by DR-TB, the TB epidemic necessitates a thorough, multi-sectoral approach. Initiatives for targeted public health education and awareness are essential to lowering the prevalence of DR-TB and improving general health outcomes in India.